2006
DOI: 10.1584/jpestics.g06-15
|View full text |Cite
|
Sign up to set email alerts
|

QSAR of 2,4-diphenyl-1,3-oxazolines for ovicidal activity against the two-spotted spider mite Tetranychus urticae

Abstract: Ovicidal activity of 2,4-diphenyl-1,3-oxazoline congeners with various substituents on the 4-phenyl ring against two-spotted spider mites Tetranychus urticae was quantitatively analyzed using the classical QSAR (HanschFujita) method. In QSAR analysis, hydrophobicity in terms of log P (P: partition coefficient between 1-octanol and water) was the most significant parameter with its square term. The optimum log P value for 2,4-diphenyl-1,3-oxazoline analogs was evaluated as about 7.1. The introduction of substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The ovicidal activity data (LC 50 ) of 90 2-(2',6'-difluorophenyl)-4-phenyl-1,3-oxazoline derivatives [7] were converted to reciprocal logarithmic values [pLC 50 ¼ À log LC 50 (M)] which have been used for the QSAR analysis. There is only one region of structural variations in the compounds, which is the R position of the phenyl ring.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The ovicidal activity data (LC 50 ) of 90 2-(2',6'-difluorophenyl)-4-phenyl-1,3-oxazoline derivatives [7] were converted to reciprocal logarithmic values [pLC 50 ¼ À log LC 50 (M)] which have been used for the QSAR analysis. There is only one region of structural variations in the compounds, which is the R position of the phenyl ring.…”
Section: Methodsmentioning
confidence: 99%
“…We have performed QSAR studies on the dataset reported by Suzuki et al [7] with 2D (physicochemical, structural, and topological) and 3D (shape, spatial, electronic, and molecular field) descriptors. The categorical list [13] of descriptors used in the development of QSAR models was reported in Table 2.…”
Section: Descriptorsmentioning
confidence: 99%
See 3 more Smart Citations